Determination of viscosity and density of fluids using frequency response of microcantilevers - Eris, Gamze; Bozkurt, Asuman Asikoglu; Sunol, Alp; Jonas, Alexandr; Kiraz, Alper; Alaca, B. Erdem; Erkey, Can (ELSEVIER SCIENCE BV, 2015)
We report on the simultaneous measurement of density and viscosity of nitrogen in gas and supercritical phases at 308.15 K and pressures up to 24 MPa. The density and viscosity were extracted from the measured frequency responses of an oscillated microcantilever immersed in N-2. To this end, a model of oscillatory motion of immersed cantilevers incorporating the effects of hydrodynamic forces was employed. Using argon as a reference fluid of known density and viscosity, cantilever calibration parameters were obtained from nonlinear regression of cantilever resonant frequencies and quality factors recorded in argon. Subsequently, these calibration parameters were used in the model equations to determine the density and viscosity of nitrogen at the given experimental pressure and temperature. In the studied pressure range, the root-mean-square deviations of the measured density and viscosity of nitrogen from the reference values obtained from NIST database were 2.5% and 5.2%, respectively. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Frequency response; Microcantilever; Density; Viscosity; Fluids; 100 MPA; TEMPERATURE; VISCOMETER; INSTRUMENT; SENSORS; LIQUID; Chemistry; Engineering